2022
DOI: 10.1017/cts.2022.400
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive capacity and preparedness of Clinical and Translational Science Award Program hubs: Overview of an environmental scan

Abstract: The ability of research networks and individual institutions to effectively and efficiently prepare, respond, and adapt to emergent challenges is essential for the biomedical research enterprise. At the beginning of 2021, a special Working Group was formed by individuals in the Clinical and Translational Science Award (CTSA) consortium and approved by the CTSA Steering Committee to explore "Adaptive Capacity and Preparedness (AC&P) of CTSA Hubs." The AC&P Working Group took a pragmatic Environmental Scan (E-Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
(50 reference statements)
0
22
0
Order By: Relevance
“…The system is able to anticipate, incorporate, and respond to changes with regards to its decision-making, governance and operational structures, and future planning Relevant challenges, lessons learned, practices that work, cases, and recommendations from CTSA hubs and other institutions are presented and discussed within the five domains of the adapted Local Adaptive Capacity (LAC) Framework. 14,15 Being overlapping, interdependent, and interacting by design, each of the domains serves a special role in hubs' adaptive capacity.…”
Section: Innovationmentioning
confidence: 99%
“…The system is able to anticipate, incorporate, and respond to changes with regards to its decision-making, governance and operational structures, and future planning Relevant challenges, lessons learned, practices that work, cases, and recommendations from CTSA hubs and other institutions are presented and discussed within the five domains of the adapted Local Adaptive Capacity (LAC) Framework. 14,15 Being overlapping, interdependent, and interacting by design, each of the domains serves a special role in hubs' adaptive capacity.…”
Section: Innovationmentioning
confidence: 99%
“…This paper is part of the Environmental Scan of Adaptive Capacity and Preparedness (AC&P) of CTSA Hubs [10], implemented by a special AC&P Working Group approved by the CTSA Steering Committee in 2021. The specific purpose of the AC&P Working Group and this scan was not to evaluate, test, generalize, quantify, or validate any hypotheses, approaches, or interventions, but rather to identify, curate, analyze, and share examples of practices, challenges, and lessons learned related to how CTSA hubs have used their expertise, resources, and collaborations to advance clinical and translational research during emergency.…”
Section: Introductionmentioning
confidence: 99%
“…The specific purpose of the AC&P Working Group and this scan was not to evaluate, test, generalize, quantify, or validate any hypotheses, approaches, or interventions, but rather to identify, curate, analyze, and share examples of practices, challenges, and lessons learned related to how CTSA hubs have used their expertise, resources, and collaborations to advance clinical and translational research during emergency. Data sources included: scientific publications and white papers on CTSAs' (and other) AC&P-related activities; a diverse sample of CTSA hubs' websites: public stories, news, highlights, measures; NCATS and other clinical and translational science organizations' websites; select CTSA hub Research Performance Progress Reports (RPPRs) de-identified information; and feedback of CTSA expert/ community reviewers and other stakeholders [10]. Local adaptive capacity for disaster preparedness was considered through the lens of five core domains of the Local Adaptive Capacity (LAC) framework [10,11]: asset base (key assets that allow hubs to respond to evolving circumstances); institutions and entitlements (an appropriate and evolving institutional environment that allows fair access to key assets and capitals); knowledge, information, learning (the ability to collect, analyze, and disseminate knowledge and information to learn in support of adaptation activities); innovation (an enabling environment to foster innovation, experimentation, and the ability to explore pragmatic solutions and opportunities); and flexible forward-looking decision-making and governance (the ability to anticipate and respond to changes with regards to its decision-making, governance and operational structures).…”
Section: Introductionmentioning
confidence: 99%
“…Informatics has directly supported the advancement of "patient care, clinical decision support, training researchers and practitioners, as well as public health surveillance and clinical research to levels that could not have been accomplished without the years of ground-laying work by the CTSAs" [3]. In 2021, the CTSA Steering Committee approved the Adaptive Capacity and Preparedness (AC&P) Working Group to identify, curate, analyze, and share examples of practices, challenges, and lessons learned related to how CTSA hubs responded and adapted to a public health crisis [4]. This paper is part of the Working Group's Environmental Scan of Adaptive Capacity and Preparedness of CTSA Hubs, which was not intended to evaluate, test, generalize, quantify, or validate any hypotheses, approaches, or interventions [4], but rather to illuminate relevant examples from CTSA hubs to help them build and augment their adaptive capacity to effectively respond to future events.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, the CTSA Steering Committee approved the Adaptive Capacity and Preparedness (AC&P) Working Group to identify, curate, analyze, and share examples of practices, challenges, and lessons learned related to how CTSA hubs responded and adapted to a public health crisis [4]. This paper is part of the Working Group's Environmental Scan of Adaptive Capacity and Preparedness of CTSA Hubs, which was not intended to evaluate, test, generalize, quantify, or validate any hypotheses, approaches, or interventions [4], but rather to illuminate relevant examples from CTSA hubs to help them build and augment their adaptive capacity to effectively respond to future events. Jones et al [5], in their presentation of the Local Adaptive Capacity (LAC) Framework, describe how understanding adaptive capacity at a local level can lead to a more comprehensive understanding at a national level.…”
Section: Introductionmentioning
confidence: 99%